Avaliação da terapia antiarrítmica com sotalol pela eletrocardiografia dinâmica de 24 horas em cães da raça boxer diagnósticados com cardiomiopatia arritmogênica do ventrículo direito - Gabriel Filho, Samuel José (2018)
Arrhythmogenic right ventricular cardiomyopathy has high incidence in the boxer dogs. They may manifest the disease at any age. Dogs can vary from asymptomatic or show clinical signs such as exercise intolerance, tachypnea, eventual syncope, congestive heart failure and sudden death, even without manifesting any of the previous clinical signs. The 24-hour dynamic electrocardiography (Holter System) is the most reliable diagnostic tool for both, diagnosis and treatment evaluation. Sotalol is a class III antiarrhythmic drug, commonly used to treat the disease in humans, however, its effects have been poorly studied in dogs. Objective: To evaluate the effect of sotalol on ventricular arrhythmias and other electrocardiographic parameters in boxer dogs diagnosed with arrhythmogenic right ventricular cardiomyopathy using the 24-hour Holter system. Materials and Methods: Retrospective study with boxers diagnosed with the disease between 2010 and 2016. Dogs were included if they had over 300 ventricularpremature complexes during the 24-hour monitoring, one Holter exam before and other after sotalol treatment, with both having at least 20-hour of monitoring. The ventricular arrhythmias and sinus pauses incidence were evaluated during sleep and wakefulness, before and after treatment. The minimum, average and maximum heart rate and the QT interval corrected by the formulas of Bazett, Fridericia, Framingham and Hodges were assessed before and after treatment. Results: Seventeen dogs comprised the study. Females were overrepresented (58,8%) and the mean presentation age for all dogs was 7.2 years + 2.0. Concerning the total daily ventricular arrhythmias, 12 animals (70.6%) showed reduction greater than 85% for ventricular tachycardia, 13 animals (76.5%) had reduction greater than 85% for ventricular couplets and 8 animals (47%) showed reduction greater than 85% for isolated ventricular premature complexes. Sinus pauses were more prevalent during sleep before and after treatment. The incidence of ventricular arrhythmias was higher during wakefulness, before and after treatment. The average and maximum heart rate decreased after treatment and no significant difference in the minimum heart rate and in the corrected QT interval was seen after sotalol treatment. Conclusion: Treatment with sotalol at a 2-2,5mg/ kg dose, twice daily promoted the significant reduction of ventricular arrhythmias as well as the average and maximum heart rate. A significant increase of sinus pauses quantity was observed after treatment. No significant difference of the minimum heart rate and the QT interval corrected by the formulas of Bazett, Fridericia, Framingham and Hodges were observed. The incidence of ventricular arrhythmias was higher during wakefulness, before and after treatment.